Label-free screening of biochemical changes in macrophage-like cells following MoS2 exposure using Raman micro-spectroscopy - Coleman, Jonathan (My University, 2021)
The emergence of large scale production techniques for 2D particulate materials has dramatically increased their applications potential. Understanding the interactions of biological cells with such particulate material is therefore of paramount importance, both for toxicological assessment and potential biomedical applications. Conventional in-vitro cytological assays commonly record only a single colorimetric end-point, and do not provide an in-depth analysis of how such materials are uptaken and processed within cells. To demonstrate its potential as an alternative, label free approach, confocal Raman micro-spectroscopy has been used to profile the cellular response of macrophage-like immune cells as a result of exposure to a sub-lethal dose of particulate MoS2, as an example novel 2D material. Particles were seen to be uptaken and trafficked in sub-cellular vesicles, and this sensitive technique allows differences in the biochemical composition of the vesicles to be assessed and monitored as a function of time. Untreated macrophage-like cells contain lipidic vesicles which are found to be relatively rich in the membrane lipid sphingomyelin, key to the process of cell membrane regeneration. After exposure to MoS2, the particulate material is seen to be invaginated in similar vesicles, the most prominent of which now, however, have spectroscopic signatures which are dominated by those of phosphatidyl family lipids, consistent with the phagocytotic pathway. The lipidic content of cells is seen to increase at all time-points (4, 24 and 72 h). although vesicles composed of sphingomyelin become more prominent again following a prolonged incubation of 72 h to a sub-lethal dose of MoS2, as the immune cell has processed the particulate material and initiates recovery to a normal/untreated state. This study reveals Raman micro-spectroscopy is an effective method for monitoring cellular responses and evolution of organelle compositions in response to MoS2 exposure. The additional benefit of using this technique is that cells can be monitored as a function of time, while it can also be used for screening other micro/nano materials for toxicology and/or establishing cell responses.
Keywords: Molybdenum disulfide; Submicrometric plates; Raman micro-spectroscopy; Vesicle identification; Lipidic vesicles; Phosphatidyl lipids; Sphingomyelin; Cellular response